The Efficacy and Prognostic Factors of the Combination of TACE and Apatinib for the Treatment of BCLC Stage C Hepatocellular Carcinoma - Liu, Shun; Liu, Kai-Cai; Lv, Wei-Fu; Lu, Dong; Zhu, Xian-Hai; Jiang, Bo; Tan, Yu-Lin; Wang, Guo-Xiang (Frontiers in Medicine, 2021)
Objective: To explore the efficacy and prognostic factors of transarterial chemoembolization (TACE) combined with apatinib in the treatment of Barcelona Clinic Liver Cancer stage C (BCLC C) hepatocellular carcinoma (HCC). Methods: Clinical data of 146 HCC patients with BCLC stage C admitted to our hospital were collected and analyzed retrospectively, of which 76 cases were treated with TACE combined with apatinib (TACE-apatinib) and 70 with TACE alone. The tumor response, survival time, and adverse events were compared between the two groups, and the factors affecting the prognosis were analyzed. Results: The objective response rate (ORR) and disease control rate (DCR) in the TACE-apatinib group were higher than in the TACE-alone group (ORR: 42.10% vs. 25.71%, P=0.03; DCR: 84.21% vs. 55.71%, P=0.001). The median time to progression (TTP) and overall survival (OS) in the TACE-apatinib group were longer than in the TACE-alone group (TTP: 5.5 months vs. 3.7 months, P=0.02; OS: 10.0 months vs. 6.2 months, P=0.01). Univariate and multivariate Cox regression analysis showed that tumor size, Child-Pugh class, and the presence of the portal vein tumor thrombus affect the prognosis of patients. Subgroup analysis revealed that TACE-apatinib therapy resulted in a higher OS in patients with tumor size <10 cm, without portal vein tumor thrombus, and with Child-Pugh class A (P<0.05). The likelihood of adverse events (hand-foot syndrome, hypertension, oral ulcer) was significantly higher in the increased in the TACE-apatinib group than in the TACE alone group (P<0.05). Conclusion: TACE-apatinib is an effective and safe method for the treatment of BCLC stage CHCC. Tumor size, Child-Pugh class, and portal vein tumor thrombus affect survival time in HCC patients with BCLC stage C.